Secure Trust Model for Peer to Peer Network - Bhandure, Roshan; Gujrathi, Siddharth; Basumatary, Jangila; Padekar, Pooja; Shirsath, Rakesh (International Journal of Computer Sciences and Engineering, 2015)
The peer to peer network has open nature which leads to exposure of various malicious activities. To eradicate these malicious activities, peers can build trust relationships among them. This paper presents distributed algorithm that enable a peer to reason about trustworthiness of other peers based on past interaction and recommendation. Using this algorithm peers will have their own adjacency trust network. Two modules of trust, service and recommendation are proposed to measure trustworthiness for providing services and giving recommendation. Interactions and recommendations are computed based on importance, recentness and peer satisfaction parameter. Also, while computing recommendation, recommender’s trustworthiness and confidence will be considered.